PENGEMBANGAN MEDIA PPT INTERAKTIF DALAM PEMBELAJARAN BAHASA INDONESIA KELAS II SD (Joyful Learning Journal, 2022)
Based on pre-research data obtained through interviews and observations It is known that the learning interest of student of class II were still low and there were a lack of media in learning Indonesian. This research was aimed to develop learning media for Bahasa Indonesia course in an Interactive PPT. The subjects in this study were 2nd grade students of SD Negeri Bintoro 4 Demak. The research was conducted in January – May 2021. The independent variable in this study was an interactive PPT learning media, the dependent variable in this study was the increase in students' interest in learning Indonesian. The research design used Research and Development. The development model used was the development model in Sugiyono 2015. The technique used test and non-test using data collecting instruments such as written test, questionnaire, interview, and documentation. The results had shown that the Interactive PPT media had been in very decent category with 87,5% percentage of material expert, 85% percentage of language expert, and 100% of media expert. Interactive PPT media was able to improve the learning outcomes from the minor scale of 15% to 100%, and the major scale of 40% to 68%. The conclusion of the research had shown that the use of Interactive PPT media was successfully developed, as well as able to improve students’ interest and learning outcomes